The Aesthetic Leadership and Its Role in Prompting the Creative Work Behaviour - Abed Alabbas, Suadad Ali; M. Ridha, Bushra Jawad; Saihood H., Ebtesam Sarhan (Opción, 2019)
The current study seeks to identify the scope of the relationship between the aesthetic leadership and the behaviour of the creative work at the University of Babylon, as an attempt by the researcher to reduce or bridge the knowledge gap between these two variables. In addition to trying to present some theo- retical and field frameworks, which enable leaders to follow a commanding style based on rationality, awareness, and intuition and this in turn enables the employees to be creative in their work regarding how to achieve the goals of the university. Accordingly, the hypothetical plan (hypothesis) of the cur- rent research dealt with the aesthetic leadership variable as an independent variable, with its three dimensions that including (rationality, awareness, and intuition), and behavior of the creative work as dependent variable with its four dimensions (exploring the opportunity, generating the idea, prompting the idea, and implementing the idea). In order to test the hypotheses of this scheme, the researcher distributed (80) questionnaires to the sample of the study. (62) Questionnaires were retrieved, with a response rate (77.5%) and after analyzing the questionnaires statistically, the results showed that there is a direct and significant correlation between the aesthetic leadership and the behavior of the creative work. Likewise, there is a positive and moral effect of the aesthetic leadership on the behavior of the creative work. Therefore, this study has presented a number of recommendations, the most important of which is the necessity of enhancing the aesthetic meanings and their applications in the administrative work, especially by leaders in various Iraqi organizations, particularly Iraqi Universities and the University in question, in order to provide an opportunity for all employees in it like supporting them with positive behaviours that are geared towards achiev- ing the set goals. Finally, the current study represents the first step towards presenting a number of future studies in the field of the aesthetic leadership and the behaviour of the creative work.